Fucoidan alleviates the mitochondria and endoplasmic reticulum stresses in ischemic rat livers - Chérifa Slim; Hana Nassrallah; Mohamed Amine Zaouali; Fatma Amara; Hatem Majdoub; Didier Morin; Hassen Ben Abdennebi (Elsevier, 2022)
Background: Hepatic ischemia reperfusion (I/R) injury remains a major problem for liver surgery leading to graft dysfunction. The use of compounds of natural origin as fucoidan, a sulfated polysaccharide from brown seaweed, could have a potential clinical benefit in the treatment of ischemic diseases. Nevertheless, the accurate mechanisms of action of fucoidan on endoplasmic reticulum (ER) stress response and mitochondria after warm hepatic ischemia have not been yet investigated. Thus, the present study focused on the modulation of fucoidan effects on the signaling pathways involving the mitochondria and the ER in ischemic rat liver. Methods: Male Wistar rats were subjected to either sham operation or one hour of partial warm ischemia (70%) followed by two hours of reperfusion. Before ischemia, rats were treated with 0.9% NaCl (I/R group), fucoidan (100 mg/kg body weight) orally for 7 consecutive days (I/R-Fuc group), TUDCA (tauroursodeoxycholic acid, inhibitor of ER stress) (100 mg / kg body weight, i.v.) 10 min before ischemia (I/R-TUDCA group) or fucoidan with TUDCA (I/R-Fuc-TUDCA group). Results: Our results showed that fucoidan and TUDCA reduced cytolysis and induced a significant improvement in antioxidant status, as compared to I/R. Interestingly, preconditioning with fucoidan resulted in significant decreased ER stress, as reflected by GRP78, p-PERK, ATF-6, XBP-1 and TRAF2. Furthermore, the phosphorylation of MAPKs (ERK, JUNK and P38) significantly diminished after fucoidan treatment. Rats undergoing fucoidan treatment protected liver against mitochondrial stress, which was correlated with low induction of apoptosis (caspase-3). Inhibition of ER stress by TUDCA administration boosted all the protective effects of fucoidan. Conclusion: In conclusion, fucoidan treatment may represent an effective strategy in reducing liver I/R injury through mitochondrial stress attenuation and ER inhibition.